Выражение (a+b/a - a+b/b) : a+b/a^2*b^2

jkh40949 jkh40949    1   24.05.2019 08:50    0

Ответы
yaku06nastyaozq1r7 yaku06nastyaozq1r7  20.06.2020 05:58
((b*(a+b)-a*(a-b))/ab)*((a^2*b^2)/(a+b)=((ab+b^2-a^2-ab)/ab)*((a^2*b^2)/(a+b)=((b^2-a^2)/ab)*((a^2*b^2)/(a+b)=((b-a)*(b+a)/ab))*((a^2*b^2)/(a+b)=ab*(b-a)=a*b^2-a^2*b
ПОКАЗАТЬ ОТВЕТЫ
KaranVahi21 KaranVahi21  20.06.2020 05:58
А+б:а^2*б^2/а+б=а^2*б^2
ну сдесь решаешь а-а уже не пишешь б/б будет 1 а после а+б сокращаешьи получантся вот так
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра